2021
DOI: 10.3389/fendo.2021.624102
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Prognostic Factors in Patients With Metastatic Adrenocortical Carcinoma Treated With Second Line Gemcitabine Plus Capecitabine Chemotherapy

Abstract: Gemcitabine plus Capecitabine (Gem/Cape) is a frequently adopted second line chemotherapy for metastatic adrenocortical carcinoma (ACC), but only a minority of patients is destined to obtain a clinical benefit. The identification of baseline predictive factors of efficacy is relevant. We retrospectively analyzed clinical data from 50 consecutive patients with metastatic progressing ACC treated between 2011 and 2019. Patients received intravenous Gemcitabine and oral Capecitabine on a metronomic schedule. Previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…PFS and OS results in this study were inferior to those observed in published trials testing other chemotherapy regimens as a second-line approach in ACC. 9 , 10 , 11 , 34 , 39 Although patient selection could have accounted for the OS differences observed, PFS is mainly influenced by treatment efficacy. The observed PFS of 1.5 months in this study is similar to the PFS of 44 and 46 days obtained in patients treated with placebo or linsitinib, respectively, in the GALACTICC study, a randomized clinical trial that failed to obtain an advantage of an insulin growth factor receptor inhibitor over placebo as a second-line approach in ACC patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PFS and OS results in this study were inferior to those observed in published trials testing other chemotherapy regimens as a second-line approach in ACC. 9 , 10 , 11 , 34 , 39 Although patient selection could have accounted for the OS differences observed, PFS is mainly influenced by treatment efficacy. The observed PFS of 1.5 months in this study is similar to the PFS of 44 and 46 days obtained in patients treated with placebo or linsitinib, respectively, in the GALACTICC study, a randomized clinical trial that failed to obtain an advantage of an insulin growth factor receptor inhibitor over placebo as a second-line approach in ACC patients.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 8 Other cytotoxic therapies, administered to patients with disease progression to EDP-M, did not show remarkable activity. 9 , 10 , 11 Molecular target therapies, attempted up to now, appeared unefficacious, 12 while immunotherapy with modern immune checkpoint inhibitors has shown some promising, results; 13 however, additional studies are needed, and strategies to overcome mechanisms of primary immune resistance of ACC should be implemented. 14 , 15 Due to their demonstrated efficacy in the management of several malignancies, taxanes have also been tested in ACC.…”
Section: Introductionmentioning
confidence: 99%
“…ACC is a rare disease, with 0.7–2 cases per million individuals [ 34 ], and it is aggressive, with two-thirds of these tumors being either grade III or grade IV at diagnosis [ 35 ]. The Median PFS of patients with locally advanced or metastatic disease receiving the currently recommended first-line schedule is 5.1 months [ 8 ], and there are few options after fist line failure. Targeted therapies are being tested in several ongoing studies.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular characterization of ACC to date uncovered the beta-catenin pathway as a potential target for therapies, in particular TP53, APC, CTNNB1, CDKN1C, IGF-2, NF1, RB1, and menin gene alterations as possible targets [ 8 ]. Beta-catenin seems to play a major role in both localized and advanced or metastatic ACC, which additionally displays ERBB4, GPCR, RAR, and PDGFR as further possible targets [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…For patients progressing after EDP-M treatment, the oncological therapeutic alternatives currently remain very limited. Several studies have evaluated various drugs/schemes, such as streptozotocin, gemcitabine in combination with capecitabine and temozolomide, and obtained modest results [ 37 , 38 , 39 ]. The need for better comprehension of the molecular pathways involved in the genesis and progression of ACC has led to the study of different target therapies.…”
Section: Standard Life-prolonging Curative Treatments For Patients Wi...mentioning
confidence: 99%